Thermoacoustic Molecular Imaging of Small Animals - Robert A. Kruger; William L. Kiser; Daniel R. Reinecke; Gabe A. Kruger; Kathy D. Miller (Molecular Imaging)
We have designed, constructed, and tested a thermoacoustic computed tomography (TCT) scanner for imaging optical absorption in small animals in three dimensions. The device utilizes pulsed laser irradiation (680–1064 nm) and a unique, 128-element transducer array. We quantified the isotropic spatial resolution of this scanner to be 0.35 mm. We describe a dual-wavelength subtraction technique for isolating optical dyes with TCT. Phantom experiments demonstrate that we can detect 5 fmol of a near-infrared dye (indocyanine green, ICG) in a 1-ML volume using dual-wavelength subtraction. Initial TCT imaging in phantoms and in two sacrificed mice suggests that three-dimensional, optical absorption patterns in small animals can be detected with an order of magnitude better spatial resolution and an order of magnitude better low-contrast detectability in small animals when compared to fluorescence imaging or diffusion optical tomography.